2012
DOI: 10.1002/dneu.22011
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans dystroglycan coordinates responsiveness of follower axons to dorsal/ventral and anterior/posterior guidance cues

Abstract: Neural development in metazoans is characterized by the establishment of initial process tracts by pioneer axons and the subsequent extension of follower axons along these pioneer processes. Mechanisms governing the fidelity of follower extension along pioneered routes are largely unknown. In C. elegans, formation of the right angle-shaped lumbar commissure connecting the lumbar and preanal ganglia is an example of pioneer/follower dynamics. We find that the dystroglycan ortholog DGN-1 mediates the fidelity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Neural expression of dgn-1 subsides after the L1 stage, with the exception of the PVP neurons in the preanal ganglion Johnson and Kramer, 2012). We reexpressed dgn-1(+) in dgn-1 null animals from transgenes under the control of various tissue-restricted heterologous gene control regions ("promoters") to determine the site of DGN-1 function in lumbar neuron maintenance (references in Materials and Methods).…”
Section: Lumbar Cell Body Maintenance Role Of Dgn-1 Requires Early Nementioning
confidence: 99%
See 4 more Smart Citations
“…Neural expression of dgn-1 subsides after the L1 stage, with the exception of the PVP neurons in the preanal ganglion Johnson and Kramer, 2012). We reexpressed dgn-1(+) in dgn-1 null animals from transgenes under the control of various tissue-restricted heterologous gene control regions ("promoters") to determine the site of DGN-1 function in lumbar neuron maintenance (references in Materials and Methods).…”
Section: Lumbar Cell Body Maintenance Role Of Dgn-1 Requires Early Nementioning
confidence: 99%
“…We recently reported that dgn-1(cg121) animals display an axon guidance defect of follower lumbar commissure axons descending from neurons of the lumbar ganglion, in which follower axons frequently fail to extend into the preanal ganglion via the lumbar commissure and instead extend along a oblique trajectory directly toward the preanal ganglion (Johnson and Kramer 2012). This lumbar axon guidance defect appears to be an independent phenotype of dgn-1(cg121) for several reasons.…”
Section: Complex Etiology Of Neural Maintenance Defectsmentioning
confidence: 99%
See 3 more Smart Citations